Can jerk cost and resultant mechanical impulse be helpful tools to discriminate swimming performance in young swimmers? - Morais, J. E.; Marinho, D. A.; Sampaio, T.; Oliveira, J. P.; Vilas-Boas, J. P.; Barbosa, T. M. (Sports Biomechanics, 2026)
The aim of this study was to compare swimming velocity, intra-cyclic variation of swimming velocity, jerk cost, and the resultant mechanical impulse in young swimmers of both sexes and by levels in the front crawl stroke. The sample included 60 young swimmers (30 boys aged 13.03 ± 0.99 years, and 30 girls aged 12.43 ± 0.90 years). Each sex group was split into two subgroups (best vs. poorest performers) of 15 swimmers each. Swimming velocity, during maximal 25 m efforts, revealed a `sex` and `level` main effect and interaction (p < 0.001). A `sex` X `level` interaction (F = 5.18, p = 0.027, n2 = 0.08) with a minimum effect size was noted for the jerk cost. Both the propulsive and resistive/braking impulses presented main effects for `level` (positive: F = 15.65, p < 0.001, n2 = 0.22; negative: F = 12.41, p < 0.001, n2 = 0.18) with a minimum effect size. Overall, the jerk cost, as well as the intra-cyclic variation in swimming velocity as indicators of motion `smoothness`, did not significantly discriminate between the best and the poorest performers in maximal 25 m efforts. Conversely, the mechanical resultant impulse did. This indicates that the mechanical resultant impulse is a strong determinant of swimming velocity in young swimmers, at least in maximal 25 m efforts.